Mitigation of supply current harmonics in fuzzy-logic based 3-phase induction motor - Arunachalam Sivakumar; Muthamizhan Thiyagarajan; Karthick Kanagarathinam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
A parallel active power filter is employed to enrich the quality of power in the power grid with non-linear loads. The induction motor drive requires better performance in many applications. The overall performance enhancement is performed by mitigating the delivery of current harmonics and related warmness losses in an induction motor. In this paper, comprehensive performance evaluation of a 3-phase induction motor is mentioned with fuzzy logic controller-based shunt active filter (SAF), and the outcomes are compared with proportional integral (PI) and proportional derivative controller (PID) controller. In this work, a new scheme of shunt active filters is connected at the supply side of the vertical speed indicator VSI fed induction motor. The simulation was performed by a fuzzy logic controller (FLC) based 3-f induction motor drive (IMD) using parallel SAF. Simulation result from MATLAB/Simulink software has been presented to understand the reduction in harmonics by introducing an active filter near the supply side. A fuzzy suitable judgment controller is brought on this work to develop the induction motor dynamic response. Analysis of the simulation outcomes, the usage of MATLAB/Simulink software program for the proposed FLC managed induction motor had been demonstrated and overall performance enhancement of induction motor was discussed.